(untitled) (Revista Brasileira Multidisciplinar, 2025)
Palliative care (PC) is defined by the World Health Organization as an approach that improves the quality of life of patients and their families facing problems associated with life-threatening illnesses. Hypodermoclysis (HDC) is considered the second main route of administration for patients undergoing PC and is mainly recommended in cases of impossibility of oral ingestion and difficult venous access. As it is considered an old practice, more medications are being tested and recommended for use via HDC. The pharmacist is the professional responsible for answering questions related to medicines and may not be properly updated and qualified on the topic. The objective of this work was to describe the new pharmaceutical recommendations for the use of medications and fluids through HDC. The review was carried out in the Medline databases; Embase; Cochrane Database; Latin American Literature in Health Sciences and Scientific Electronic Library Online, including publications in any language from 2015 onwards. The exclusion criteria was articles on HDC in pediatric PC and articles that contain only technical information involving this route. The search resulted in 872 articles. Of these, 67 were fully analyzed, 42 of which were included. The summary of the new pharmaceutical recommendations regarding the administration of medications and fluids via HDC can help guide this professional in clarifying doubts and making evidence-based decisions, promoting the optimization of pharmacotherapy for patients under PC.